2014
DOI: 10.1016/j.bbagrm.2014.04.022
|View full text |Cite
|
Sign up to set email alerts
|

The T box riboswitch: A novel regulatory RNA that utilizes tRNA as its ligand

Abstract: The T box riboswitch is a cis-acting regulatory RNA that controls expression of amino acid-related genes in response to the aminoacylation state of a specific tRNA. Multiple genes in the same organism can utilize this mechanism, with each gene responding independently to its cognate tRNA. The uncharged tRNA interacts directly with the regulatory RNA element, and this interaction promotes readthrough of an intrinsic transcriptional termination site upstream of the regulated coding sequence. A second class of T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…In addition, tRNAs and tRNA-derived fragments also serve regulatory roles in E. coli 1,2 and other bacteria (recently reviewed in refs. 3,4 ). For example, in E. coli , uncharged tRNA at the ribosomal A-site is the signal that stimulates RelA to produce guanosine tetraphosphate (ppGpp), which initiates the stress response to amino acid starvation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tRNAs and tRNA-derived fragments also serve regulatory roles in E. coli 1,2 and other bacteria (recently reviewed in refs. 3,4 ). For example, in E. coli , uncharged tRNA at the ribosomal A-site is the signal that stimulates RelA to produce guanosine tetraphosphate (ppGpp), which initiates the stress response to amino acid starvation.…”
Section: Introductionmentioning
confidence: 99%
“…The apical region of Stem I contains the conserved AG bulge and terminal loop (6), which interdigitate to create a platform that interacts with the tRNA elbow in the glycyl-tRNA synthetase gene (glyQS) T box RNA (18,21). However, it is unclear whether glyQS structural information is generally applicable to other T box RNAs because of the absence of the Stem II and IIA/B conserved domains (15) and an unusual arrangement of sequences in the apical portion of Stem I that differs from the consensus T box arrangement (22).…”
mentioning
confidence: 99%
“…The SL codon is followed by the conserved purine which is a guanosine (instead of adenosine in B. subtilis and G. kaustophilus). As has been described for the B. subtilis glyQS T-box, the characteristic stem II and pseudoknot stem IIA/B are also absent from S. aureus glyS T-box (Henkin 2014). It has been proposed that the absence of stem II and pseudoknot stem IIA/B indicates that no additional trans-acting factors mediate the binding of the T-box with the tRNA Gly (Grundy and Henkin 2004;Vitreschak et al 2008).…”
Section: Identification Of the Glys Leader Sequence And Transcriptionmentioning
confidence: 80%
“…They control transcription of downstream genes that either encode proteins involved in biosynthesis and transport of aa or aminoacyl-tRNA synthetases (aaRSs) which supply ribosomal protein synthesis with the aminoacylated tRNAs (aa-tRNAs) substrates (Henkin 2008(Henkin , 2014. Although their main regulatory mechanism is transcriptional attenuation, recently it was shown that the ileS T-box in Actinobacteria acts via sequestration of the Shine-Dalgarno sequence, thus modulating ribosome binding and translation initiation (Sherwood et al 2015).…”
Section: Introductionmentioning
confidence: 99%